Design optimisation of hazardous waste disposal facilities through the application of water balance and mass transport modelling - Turner, Robert Shane (University of the Free State, 2011)
Although the country’s legislation emphasizes the importance of waste prevention, recovery and re-use, waste disposal currently forms the basis of waste management within South Africa. Due to the lack of facilities as well as the high cost of waste disposal by incineration, the most common form of organic and inorganic waste disposal in South Africa is by landfill. Waste disposal by landfill may be cost effective and is environmentally acceptable if carried out correctly and appropriately. The prime environmental media that are affected by waste disposal by landfill are typically water and air, of which ground water forms one of the major migration pathways for contaminants. Ground water is one of South Africa’s major water resources and it is thus of utmost importance that the countries ground water resource be protected. The greatest threat posed by modern landfills to the ground water environment is the leachate that is generated at the base of the landfill disposal facility. This leachate consists essentially of water-soluble compounds that accumulate in association with infiltrating water as it percolates through the waste. The quality of this leachate is variable and due to the processes by which certain wastes are generated, may contain elements that could potentially have an adverse impact on the environment if the waste is not disposed of correctly. All waste is required to be assessed and appropriately disposed of, as currently formalized in the Department of Water Affairs and Forestry’s, Waste Management Series, Second Edition 1998 - Minimum Requirement Documents. These documents classify waste into two classes, namely general waste and hazardous waste, according to the toxological risk that the waste poses on contaminating the environment. The Minimum Requirement Documents have proposed 10 different landfill liner designs which are required to be installed at landfill disposal facilities according to the classification of the waste. The two landfill liner designs that are suitable for hazardous waste disposal are required to entail significant leachate interception and removal systems, irrespective of the site water balance or site specific conditions and are thus often unrepresentative for the specific disposal facility. Use was made of site specific parameters, such as the required site water balance, geochemical composition and analyses of the slag, physical properties of the slag material as well as the efficiency of the layers within the liner design, to determine the most optimal liner design for the slag disposal facility investigated. Slag in an inorganic metallurgical waste that is generically produced at ferrochrome producing plants in South Africa. Slag is disposed of by means of landfill as a dry aggregate material with an average grain size of 20 mm. The risk that the slag disposal facility posed on contaminating the environment was assessed in accordance with the current environmental legislation and the optimized liner design was determined. The optimized liner design for the 50 ha slag disposal facility investigated consists of 4 layers and is capable of capturing the required volume of leachate in order to optimally protect the environment from any adverse effects caused by the leachate. The liner has thus been designed according to the Best Practicable Environmental Option norm and at the most optimal cost.
Dissertation (M.Sc. (Institute for Groundwater Studies)--University of the Free State, 2011
Keywords: Hazardous wastes; Waste disposal in the ground; Water -- Pollution; Aquifers; Landfill classification; Landfill liner design; Mass transport modelling; Minimum requirement documents; MODFLOW; Waste characterization and classification; Water balance